ANALISIS PUISI “RAHASIA HUJAN” KARYA HERI ISNAINI DENGAN MENGGUNAKAN PENDEKATAN MIMETIK - Nurlaela Tussaadah; Teti Sobari; Aditya Permana (IKIP Siliwangi, 2020)
Poetry is an imaginative literary work, which analogizes meaning with other expressions so that the meaning contained in poetry is hidden behind aesthetic and fictional words that not everyone understands the direction and purpose of the poem delivered. Poetry is not easily understood by the reader at a glance because the language is broad and the meaning is difficult to interpret, therefore a reader must have the knowledge in studying poetry literary works in order to understand the meaning conveyed from the poem. The poem